Chemical zoning of muscovite megacrystal from the Brazilian Pegmatite Province - Viana,Rúbia R. (2007)
Macroscopically homogenous muscovite plate from the Cruzeiro pegmatite, located in the Eastern Pegmatite Province in Minas Gerais, may show complex distribution patterns of some trace elements. In geochronological and petrological studies, as for example in the distinction of magmatic and post-magmatic mica, the cause of zoning could be taken into consideration. The complex chemical zoning in the studied mica plate can be best explained by growth in an evolving magma followed by alteration due to percolation of hydrothermal fluids. Enrichment of Rb towards the border is interpreted as resulting from the chemical evolution of the residual magma during crystal growth. The depletion in (IV Al+VI Al) as well as the increase in (Fe+Mg) and Si along a fracture could be due to the hydrothermal celadonitic substitution of muscovite. This alteration also caused depletion in the contents of Rb, Ga, Y, Nb, Sn, and Zn and residual concentration of Ti. Elements such as Ga, Y, Nb, Sn, and Zn, rarely considered in the discussion of differentiation or alteration processes in micas, have been shown to be as significant as the alkali-elements.